Control and Surveillance Operations to Prevent Chronic Wasting Disease Establishment in Free-Ranging White-Tailed Deer in Québec, Canada - Gagnier, Marianne; Laurion, Isabelle; DeNicola, Anthony J. (Animals (Basel), 2020)
Chronic wasting disease (CWD), a degenerative and fatal prion disease affecting cervids, was detected for the first time in the province of Québec, Canada, in a red deer (Cervus elaphus) farm in the Laurentides region on 10 September 2018. To assess CWD prevalence and control the disease in the free-ranging white-tailed deer (Odocoileus virginianus) population, a response plan including enhanced surveillance, population control, regulatory measures, and public outreach was deployed by the Ministry of Forests, Wildlife, and Parks (MFFP). In the 401 km2 white-tailed deer control area, a total of 750 free-ranging white-tailed deer were culled over 70 days, from 22 September to 15 December 2018. Of the culled deer, 534 were tested for CWD. We also tested for CWD a total of 447 white-tailed deer hunted from the enhanced surveillance zone and 2584 free-ranging white-tailed deer harvested outside this zone. Regulations were applied to prevent the spread of the disease through movements of infected animals harvested by hunters. Although no case of CWD was detected in free-ranging cervids in Québec in 2018, this does not confirm the absence of the disease in these populations. However, the results suggest that if CWD is present, few free-ranging cervids are infected, making it possible to prevent its establishment in the province of Québec.